Three Novel Herpesviruses of Endangered Clemmys and Glyptemys Turtles - Ossiboff, Robert J. (PLoS One, 2015)
The rich diversity of the world’s reptiles is at risk due to significant population declines of broad taxonomic and geographic scope. Significant factors attributed to these declines include habitat loss, pollution, unsustainable collection and infectious disease. To investigate the presence and significance of a potential pathogen on populations of critically endangered bog turtles (Glyptemys muhlenbergii) as well sympatric endangered wood (G. insculpta) and endangered spotted (Clemmys guttata) turtles in the northeastern United States, choanal and cloacal swabs collected from 230 turtles from 19 sites in 5 states were screened for herpesvirus by polymerase chain reaction. We found a high incidence of herpesvirus infection in bog turtles (51.5%; 105/204) and smaller numbers of positive wood (5) and spotted (1) turtles. Sequence and phylogenetic analysis revealed three previously uncharacterized alphaherpesviruses. Glyptemys herpesvirus 1 was the predominant herpesvirus detected and was found exclusively in bog turtles in all states sampled. Glyptemys herpesvirus 2 was found only in wood turtles. Emydid herpesvirus 2 was found in a small number of bog turtles and a single spotted turtle from one state. Based on these findings, Glyptemys herpesvirus 1 appears to be a common infection in the study population, whereas Glyptemys herpesvirus 2 and Emydid herpesvirus 2 were not as frequently detected. Emydid herpesvirus 2 was the only virus detected in more than one species. Herpesviruses are most often associated with subclinical or mild infections in their natural hosts, and no sampled turtles showed overt signs of disease at sampling. However, infection of host-adapted viruses in closely related species can result in significant disease. The pathogenic potential of these viruses, particularly Emydid herpesvirus 2, in sympatric chelonians warrants additional study in order to better understand the relationship of these viruses with their endangered hosts.